Bacterial cellulose production from food waste - Chua, Gek Kee (2020)
The objectives of this project is to investigate the feasibility of using food wastes for bacterial cellulose production, where the best pretreatment methods were identified and the effect of carbon and nitrogen sources variation together with the operating conditions were examined. Food wastes were collected from the café inside the Gambang Campus of Universiti Malaysia Pahang. After screening and grinding, food wastes were subjected to pretreatment in order to hydrolyze the nutrients. Three methods were employed, they are hydrothermal pretreatment, alkaline pretreatment and enzymatic pretreatment. The performance of the pretreatment was monitored using Bradford assay (protein content), phenol-sulphuric acid assay (carbohydrate content) and Bligh & Dyer method (lipid content). Food wastes hydrolysate (FWH) obtained after hydrothermal pretreatment was used as fermentation medium to produce bacterial cellulose by Gluconacetobacter xylinus. The effect of carbon and nitrogen content in the FWH was studied by varying the composition of the food wastes collected before pretreatment. While the operating conditions studied were inoculum density, temperature, pH and stirring speed. The yield of bacterial cellulose (BC) produced was monitored together with its ability to hold water. The physical property of BC was characterized with FTIR and morphological property was observed using SEM. Hydrothermal and enzymatic pretreatments were found to solubilize more nutrients into the solution. Increase in carbon content will increase BC yield provided that nitrogen content is not a limiting factor. The optimal operating conditions to produce BC were found to be at 30C, pH 5.5, 10% inoculum density and 150 rpm stirring speed. BC produced using FWH has a similar physical property as that of Nata de Coco. From the SEM results, BC from FWH has a similar microfibril networks as the BC produced from pineapple juice. Nevertheless, it is denser with some impurities trapped in the network. Thus, further pretreatment may be required if the quality of BC is to be increased.